VD_FINDINFO Arrêt / 2010 / 1165 vom 4. August 2010 - VD Tribunal cantonal (2010)
PRIVATION DE LIBERTÉ À DES FINS D'ASSISTANCE, MALADIE MENTALE, URGENCE, SCHIZOPHRÉNIE | 369 CC, 397a al. 1 CC, 398a CPC, 398d CPC